2012
DOI: 10.1287/opre.1120.1054
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Under Probabilistic Envelope Constraints

Abstract: Chance constraints are an important modeling tool in stochastic optimization, providing probabilistic guarantees that a solution "succeeds" in satisfying a given constraint. Although they control the probability of "success," they provide no control whatsoever in the event of a "failure." That is, they do not distinguish between a slight overshoot or undershoot of the bounds and more catastrophic violation. In short, they do not capture the magnitude of violation of the bounds. This paper addresses precisely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…Calafiore and El Ghaoui [14] employ various statistical bounds to approximate robust individual chance constraints where the ambiguity set specifies structural properties such as radial symmetry, unimodality or independence. Bertsimas et al [8] use statistical hypothesis tests to approximate robust individual chance constraints when the ambiguity set has to be estimated from samples of the unknown distribution Q. Xu et al [57] employ a generalized Chebyshev inequality to derive tractable reformulations of problems with probabilistic envelope constraints, which enforce robust chance constraints at all tolerance levels ∈ [0, 1). Instead of relying on statistical results, one can also employ duality of moment problems [10] to derive tractable reformulations of robust individual chance constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Calafiore and El Ghaoui [14] employ various statistical bounds to approximate robust individual chance constraints where the ambiguity set specifies structural properties such as radial symmetry, unimodality or independence. Bertsimas et al [8] use statistical hypothesis tests to approximate robust individual chance constraints when the ambiguity set has to be estimated from samples of the unknown distribution Q. Xu et al [57] employ a generalized Chebyshev inequality to derive tractable reformulations of problems with probabilistic envelope constraints, which enforce robust chance constraints at all tolerance levels ∈ [0, 1). Instead of relying on statistical results, one can also employ duality of moment problems [10] to derive tractable reformulations of robust individual chance constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Vandenberghe et al [37] later showed that (P) admits an exact reformulation as a single SDP whenever Ξ is described through linear and quadratic inequalities and P contains all distributions sharing the same first and second-order moments. The resulting generalized Chebyshev bounds are widely used across many different application domains, ranging from distributionally robust optimization [9] to chance-constrained programming [8,39,43], stochastic control [36], machine learning [16], signal processing [38], option pricing [1,13,18], portfolio selection and hedging [40,44], decision theory [33] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ambiguity sets of special interest include the Markov ambiguity set containing all distributions with known mean and support [48], the Chebyshev ambiguity set containing all distributions with known bounds on the first and second-order moments [12,14,22,31,39,46,49,51,52], the Gauss ambiguity set containing all unimodal distributions from within the Chebyshev ambiguity set [38,41], various generalized Chebyshev ambiguity sets that specify asymmetric moments [12,13,35], higher-order moments [7,30,45] or marginal moments [17,18], the median-absolute deviation ambiguity set containing all symmetric distributions with known median and mean absolute deviation [24], the Huber ambiguity set containing all distributions with known upper bound on the expected Huber loss function [15,48], the Wasserstein ambiguity set containing all distributions that are close to the empirical distribution with respect to the Wasserstein metric [19,34,40], the KullbackLeibler divergence ambiguity set and likelihood ratio ambiguity set [10,26,27,31,47] containing all distributions that are sufficiently likely to have generated a given data set, the Hoeffding ambiguity set containing all component-wise independent distributions with a box support [3,8,10], the Bernstein ambiguity set containing all distributions from within the Hoeffding ambiguity set subject to marginal moment bounds [36], several φ-divergence-based ambiguity sets [2,…”
mentioning
confidence: 99%